BUSINESS JUDGEMENT RULE DIKAITKAN DENGAN TINDAK PIDANA KORUPSI YANG DILAKUKAN OLEH DIREKSI BADAN USAHA MILIK NEGARA TERHADAP KEPUTUSAN BISNIS YANG DIAMBIL - Frans Affandhi; Bismar Nasution; Mahmul Siregar; Mahmud Mulyadi (Universitas Sumatera Utara, 2016)
ABSTRACT When the SOE Board of Directors took the decision to run the company with the aim of seeking a profit, then the decision that will contain the business implications and legal implications. If it turns out, the decision was made a loss-making state enterprises fail or raised, then the SOE Board of Directors should not be prosecuted by the Anti-Corruption Act. This is because in the business world there are rules Business Judgment Rule (BJR) which regulates the sanctions to the Board of Directors. Such liability can not be sought from the Board of Directors of SOEs if: 1) The loss is not due to error or negligence; 2) It has been doing the maintenance of good faith and prudence for the benefit and in accordance with the purposes and objectives of the company; 3) There is a conflict of interest, either directly or indirectly, for the management of the resulting losses; and 4) have taken action to prevent and arising or continuing losses. Keywords : Business Judgment Rule; Directors of State Own Enterprise; Decision Maker